Modificação por nitretação a plasma das superfícies dos aços AISI-4140, AISI-420C e DIN16MnCr5 - Zambon, Marcel Fabiano (2011)
Plasma nitriding is a surface modification technique used for improving hardness, wear resistance, and fatigue. In this work, samples of AISI-4140, DIN16MnCr, and AISI-420C steels were heat treated, forming martensitic structures, and then were submitted to plasma nitriding for 5 hours at 400, 450, and 500oC, under a hydrogen and nitrogen gas mixture having a pressure of 5 mbar. The samples were characterized by hardness tests, optical microscopy, scanning electron microscopy and X-ray diffraction. There has been an increase in surface hardness as expected from the literature. The rise of nitriding temperature produced an increase in the surface layers thickness. The results obtained show a compact layer composed of Fe4N nitrides and CrN nitrides, identified by X-ray diffraction, characterizing the hardness. With these nitriding temperatures, there was a decrease in hardness caused by the annealing.